PENDIDIKAN TOLERANSI ANTARSESAMA PADA BUDAYA TORON TANA BEJI’ MASYARAAT MADURA: PENDIDIKAN TOLERANSI ANTARSESAMA PADA BUDAYA TORON TANA BEJI’ MASYARAAT MADURA - Rahem, Zaitur (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2020)
Abstract Tolerance education is one of the most important campaigns in Indonesia. this is to stem the existence of radicalization and anarchic movements in the name of religious and cultural symbols today. Tolerance education from all social sources of Indonesian society needs to always be addressed. At the very least, a portrait of the tolerance of the people in all regions of the country will strengthen the reason and tolerance of the people in Indonesia. Like a portrait of tolerance education in the culture of toron tana beji 'in the Madurese community. Through an ethnographic approach and qualitative study, tolerance education in the culture of the toron tana beji 'among the Madurese is very real binding on good relations between the ummat in the interior. Key word: Toleransi, Madura, Toron tana beji’